Peningkatan partisipasi belajar ipa melalui model pembelajaran mind mapping pada siswa kelas ivSd negeri 01 sudimoro tahun 2015/2016 - Choirin Nissa, Anifa (2016)
This study aims to increase participation to learn science through learning model Mind Mapping in the fourth grade students of SD Negeri 01 Sudimoro 2015 / 2016. This research is a class act. Prior to the act of cooperation and involvement of students in the group 38.70%, responding to other people's opinion amounted to 35.48%, the task assigned by the teacher at 61.29%, dare to do the problems in front of the class amounted to 45.16% , In the first cycle there is increasing cooperation and involvement of students in the group amounted to 61.29%, responding to other people's opinion amounted to 54.83%, the task assigned by the teacher at 72.58, courageous work on the problems in front of a class of 62, 90. In the second cycle of cooperation and involvement of students in the group increased by 82.25%, giving response to the opinions of others increased by 74.19%, the task assigned by the teacher increased to 88.70%, dare to do the work in front of the class increases 82.25. In addition to increased participation learning learning outcomes of each cycle also increased before their actions amounted to 43.38%, in the first cycle increased to 69.91 and the second cycle increased by 74.19%. Based on the research that has been done can be concluded that Mind Mapping learning model can improve students' participation in science subjects fourth grade students of SD Negeri 01 Sudimoro year 2015/2016.